2015
DOI: 10.35536/ljb.2015.v3.i2.a5
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Grade Incentives and Gender on Student Performance: An Experiment

Abstract: This experiment was conducted to determine the impact of grade incentives and gender on student performance at the university level. We perform a two-way analysis of variance on a sample of three groups of students taking a first-year core mathematics course and another three groups taking a fourth-year compulsory accounting course. We find that grade incentives significantly affect student performance for both sampled courses across all six groups. Gender is found to significantly affect the performance of ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
0
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 13 publications
0
0
0
Order By: Relevance
“…Our results are consistent with other studies by Levitt et al, and Gneezy (1,4). Levitt found that financial incentives helped males and older students perform better on standardized math and reading tests (1).…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…Our results are consistent with other studies by Levitt et al, and Gneezy (1,4). Levitt found that financial incentives helped males and older students perform better on standardized math and reading tests (1).…”
Section: Discussionsupporting
confidence: 93%
“…This is unlike a reading test, where no matter how much the answer is desired if the reading can't be understood, no answer will be found. Also, the value placed on the student's relationship with math must be taken into account (4). For our study, we used students who have previously taken Algebra 2 or are currently taking Algebra 2, with mostly honors classes to make sure they knew the concepts tested.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation